Día de los Muertosin Mexico: A folkcomunicacional analysis (Revista Internacional de Folkcomunicação, 2019)
Día de los Muertos. Día de los Muertos is a representative event of Mexican culture and recognized worldwide. It is a cultural manifestation of great significance, because it is a mixture of cultures and also shows the way Mexicans deal with death. The objective of this work is to analyze, through observation, the manifestations that make up the period that comprises this event, which runs from the end of October until the beginning of November, with the celebrations closed on 02, day of the dead / dead. For that, the theory of Folkcommunicação was used to understand such manifestations under socio-cultural and, mainly, communicational bias, since it is a manifestation that communicates to the world what is the death in Mexico. Communication. Culture. Folkcomunicação.